Production of Glucoamylase by Aspergillus oryzae MTCC152 in Solid State Fermentation - Mishra A.; Debnath Das M. (My University, 2025)
Aspergillus oryzae MTCC152 produced significant amount of glucoamylase using inexpensive agricultural materials in solid state fermentation. Bran of wheat and pulses such as Cajanus cajan and Vigna mungo were used to test their efficiency as sole carbon source for enzyme production. Maximum enzyme activity was obtained with SSF of wheat bran after 96 h at initial pH of 4.8 and 30°C temperature. The optimum temperature and pH for enzyme activity were 50°C and 5 respectively.